Early essential newborn care is associated with improved newborn outcomes following caesarean section births in a tertiary hospital in Da Nang, Vietnam: a pre/post-intervention study. Issue 3 (22nd July 2021) - Tran, Hoang Thi; Murray, John Charles Scott; Sobel, Howard Lawrence; Mannava, Priya; Huynh, Le Thi; Nguyen, Phuong Thi Thu; Giang, Hoang Thi Nam; Le, Tuyen Thi Mong; Hoang, Tuan Anh; Nguyen, Vinh Duc; Li, Zhao; Pham, Nga Thi Quynh
Abstract : Background: To improve maternal and neonatal outcomes, Vietnam implemented early essential newborn care (EENC) using clinical coaching and quality improvement self-assessments in hospitals to introduce policy, practice and environmental changes. Da Nang Hospital for Women and Children began EENC with caesarean section births to inform development of national guidelines. This study compared newborn outcomes after caesarean sections pre/post-EENC introduction. Methods: Maternity records of all live in-born hospital caesarean births and separate case records of the subpopulation admitted to the neonatal intensive care unit (NICU) were reviewed pre-EENC (November 2013–October 2014) and post-EENC (November 2014–October 2015) implementation. NICU admissions and adverse outcomes on NICU admission were compared using descriptive statistics. Findings: A total of 16 927 newborns were delivered by caesarean section: 7928 (46.8%) pre-EENC and 8999 post-EENC (53.2%). Total NICU admissions decreased from 16.7% to 11.8% (relative risk 0.71; 95% CI 0.66 to 0.76) after introduction of EENC. Compared with the pre-EENC period, babies with hypothermia on admission to the NICU declined from 5.0% to 3.7% (relative risk 0.73; 95% CI 0.63 to 0.84) and cases of sepsis from 3.2% to 0.8% (relative risk 0.26; 95% CI 0.20 to 0.33) post-EENC implementation. While more than half of all newborns in the NICU were fed something other than breastmilk pre-EENC introduction, 85.8% were exclusively breast fed post-EENC (relative risk 1.86; 95% CI 1.75 to 1.98). Preterm newborns <2000 g receiving kangaroo mother care (KMC) increased from 50% to 67% (relative risk 1.33; 95% CI 1.12 to 1.59). Conclusion: The EENC quality improvement approach with caesarean section births was associated with reduced NICU admissions, admissions with hypothermia and sepsis, and increased rates of exclusive breast feeding and KMC in the NICU.